Behavioral interventions motivate action to address climate change - Alyssa H. Sinclair; Danielle Cosme; Kirsten Lydic; Diego A. Reinero; José Carreras-Tartak; Michael E. Mann; Emily B. Falk (Proceedings of the National Academy of Sciences, 2025)
Mitigating climate change requires urgent action at individual, collective, and institutional levels. However, individuals may fail to act because they perceive climate change as a threat that is distant or not personally relevant, or believe their actions are not impactful. To address these psychological barriers, we conducted a large-scale “intervention tournament.” In a sample of 7,624 participants, we systematically tested 17 interventions that targeted psychological mechanisms described by three key themes: Relevance, Future Thinking, and Response Efficacy. Interventions that emphasized social relevance were the most effective for motivating people to share news articles and petitions about climate change. Interventions that targeted future thinking were the most effective for broadly motivating individual actions (e.g., driving less, eating vegetarian meals) and collective actions (e.g., donating, volunteering) to address climate change. Interventions that emphasized the environmental impact of these actions reliably increased the perceived impact of pro-environmental actions, but did not consistently motivate action. Notably, interventions that targeted two or more mechanisms—such as imagining a future scenario that involved oneself or close others—were most effective. Importantly, our leading interventions were substantially more effective than prevalent existing strategies (e.g., carbon footprint information). Our findings are relevant to theories of behavior change, motivation, and information sharing, with potential applications across domains. Insights from our tournament could be applied to develop scalable online interventions and mass communication campaigns to address climate change.